Pemetaan Dan Perhitungan Pemaparan Tingkat Kebisingan Pada Industri Pengolahan Kayu Di Kecamatan Siak, Provinsi Riau - Aryo Sasmita; Muhammad Reza; Rodesia Mustika Rozi (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2021)
In its operational activities, CV. X, which is engaged in wood processing, has the potential to cause noise from machines used in the pallet production process. Noise in this company can affect the health and comfort of workers. This study aims to determine the intensity of noise produced by the production machine, the length of time of exposure, noise mapping and noise control efforts. The noise measurement method refers to the noise mapping method and the instrument used is the Sound Level Meter (SLM). The data obtained were then processed into contour maps with variations in blue, green, yellow, purple and red. The results showed the highest noise level was 99.4 dB and the lowest noise level was 67,3 dB. Based on the results of calculations using the NIOSH equation from 128 measurement points of the noise mapping method, there are 38 points with a noise level> 85 dB which indicates the exposure time is above the standard recommended by NIOSH. The highest noise level was 99.4 dB with an exposure time of 0,3 hours and the lowest noise level was 67.3 dB with an exposure time of 475 hours. Control measures that can be made to reduce noise include control from sources, transmission lines, and receivers.